Peritoneal carcinomatosis in metastatic Non-Small Cell Lung Cancer: review of the literature - Fausto Meriggi; Sara Cherri; Diego Gavezzoli; Tony Sabatini; Claudio Bna′; Alberto Zaniboni (Cancer and Metastasis Reviews, 2026)

On the role of bacterial gut microbiota from supralittoral amphipod Talitrus saltator (Montagu, 1808) in bioplastic degradation - Alessandro Russo; Aldo D'Alessandro; Monica Di Paola; Benedetta Cerasuolo; Sonia Renzi; Niccolò Meriggi; Luca Conti; Jessica Costa; Rebecca Pogni; Tania Martellini; Alessandra Cincinelli; Alberto Ugolini; et al. (Science of The Total Environment, 2025)

Dispersal and settlement dynamics of wolves in a lowland ecological corridor in northern Italy: Effects of resource availability and human disturbance - Camilla De Feudis; Elisa Torretta; Valerio Orioli; Pietro Tirozzi; Luciano Bani; Alberto Meriggi; Olivia Dondina (Biological Conservation, 2025)

Population trend and distribution of mountain (Lepus timidus) and brown hares (Lepus europaeus) in Central Alps (N-Italy, 1980–2020) - Greta Martino; Gianpasquale Chiatante; Maria Ferloni; Alberto Meriggi (European Journal of Wildlife Research, 2024)

Habitat selection and density of common pheasant (Phasianus colchicus) in Northern Italy: effects of land use cover and landscape configuration - Gianpasquale Chiatante; Alberto Meriggi (European Journal of Wildlife Research, 2022)
Knowing the ecology of game species is important to define sustainable hunting pressure and to plan management actions aimed to maintain viable populations. Common pheasant ( Phasianus colchicus ) is one of the main gamebird species in Europe and North America, despite its native range extending from the Caucasus to Eastern China. This research aimed to define the environmental variables shaping the spatial distribution of male pheasants and to estimate their breeding density in an agroecosystem of northern Italy. During the breeding season, 2015, we carried out 372 point counts with unlimited distances, randomly placed following a stratified sampling survey design. The habitat requirements of the pheasant were evaluated following a presence vs. availability approach, using environmental variables related to land use cover and landscape configuration. We built generalized linear models with a binary distribution, selecting variables following an information-theoretic approach. Densities were estimated through both conventional and multiple-covariate distance sampling. We estimated a density of 1.45 males/km 2 , with 4.26 males/km 2 in suitable areas and 0.91 males/km 2 in unsuitable ones. We found pheasants in areas with meadows and tree plantations, which were used to find food and refuges from predators and bad weather conditions. Similarly, woodlands have a positive effect on species occurrence, whereas arable lands were avoided, specifically maize and paddy fields. We found little evidence that landscape configuration affects pheasant occurrence. We found pheasants to be negatively affected by the length of edges between woodlands and arable lands, whereas edges between woodlands and grasslands seem to be beneficial for the species. These findings could help landscape and wildlife managers to plan habitat improvement actions useful to maintain self-sustaining populations of this species, by increasing cover of woodlands, meadows, and tree plantations.

Factors affecting the crop damage by wild boar (Sus scrofa) and effects of population control in the Ticino and Lake Maggiore Park (North-western Italy) - Fabrizio Cappa; Luciano Bani; Alberto Meriggi (Mammalian Biology, 2021)
Wild boar foraging impacts the crops, pastures, and meadows causing remarkable losses to agricultural income. Protected areas located in plains, such as the Ticino Valley Natural Park, are characterized by the coexistence of important natural habitats and intensive agricultural areas. In the Park, from 2010 to 2017, 49% of the complaints report an event of damage to maize and 43% to meadows. The total expense for reimbursements of the maize amounted to € 439,341.52, with damages concentrated in May, after sowing period and between August and September, during the milky stage of maize. For meadows reimbursements amounted to € 324,768.66, with damage events concentrated in February and March. To reduce damage to crops, the Park administration carried out lethal control of the wild boar population. From 2006 to 2017, the most used control method was culling from hunting hides. In our analysis, we did not find significant relationships between the number of shot boars and the damage amount. The factors that determine the decrease of damage probability to crops are mainly related to human disturbance and the characteristics of the fields. The predictive model of damage risk built comparing damaged and undamaged fields showed a good predictive ability. The population viability analyses showed that it is impossible to obtain a drastic reduction of population with the current harvest rate. By tripling it and focusing on the females and sub-adult a numerical reduction of 50% of the population would be achievable in 7 years and the probability of population survival would be halved in 3 years.

Spatial distribution of the Barbary Partridge (Alectoris barbara) in Sardinia explained by land use and climate - Gianpasquale Chiatante; Marta Giordano; Anna Vidus Rosin; Oreste Sacchi; Alberto Meriggi (European Journal of Wildlife Research, 2021)
A bstract More than half of the European population of the Barbary Partridge is in Sardinia; nonetheless, the researches concerning this species are very scarce, and its conservation status is not defined because of a deficiency of data. This research aimed to analyse the habitat selection and the factors affecting the abundance and the density of the Barbary Partridge in Sardinia. We used the data collected over 8 years (between 2004 and 2013) by spring call counts in 67 study sites spread on the whole island. We used GLMM to define the relationships between the environment (topography, land use, climate) both the occurrence and the abundance of the species. Moreover, we estimated population densities by distance sampling. The Barbary Partridge occurred in areas at low altitude with garrigue and pastures, avoiding woodlands and sparsely vegetated areas. We found a strong relationship between the occurrence probability and the climate, in particular, a positive relation with temperature and a negative effect of precipitation, especially in April–May, during brood rearing. Furthermore, dry crops positively affected the abundance of the species. We estimated a density of 14.1 partridges per km 2 , similar to other known estimates. Our findings are important both because they increase the knowledge concerning this species, which is considered data deficient in Italy, and because they are useful to plan management actions aimed to maintain viable populations if necessary.

Spatial distribution of the pine marten (Martes martes) and stone marten (Martes foina) in the Italian Alps - Federica Fonda; Gianpasquale Chiatante; Alberto Meriggi; Andrea Mustoni; Marco Armanini; Andrea Mosini; Arianna Spada; Marco Lombardini; Davide Righetti; Marco Granata; Enrica Capelli; Renato Pontarini; et al. (Mammalian Biology, 2021)

First assessment of habitat suitability and connectivity for the golden jackal in north-eastern Italy - Elisa Torretta; Olivia Dondina; Claudio Delfoco; Luca Riboldi; Valerio Orioli; Luca Lapini; Alberto Meriggi (Mammalian Biology, 2020)
Compared with the rapid expansion across Europe, the golden jackal colonization of Italy is still limited and slow. No study focused on the habitat selection or landscape connectivity for this species was performed in Italy; thus, the potential distribution and dispersal patterns in the country remain unknown. Our objectives were to evaluate the suitability of the Friuli-Venezia Giulia region (north-eastern Italy) for the golden jackal, as well as to identify the ecological corridors connecting the areas currently occupied by the species. Corridors modelling allowed us both to hypothesize the dispersal dynamics occurring in the study region and to identify possible obstacles to future range expansion. We surveyed golden jackal presence in two study areas, covering an area of 500 km 2 , from March 2017 to February 2018. Using collected data, we modelled the species home-range scale habitat suitability based on an ensemble modelling approach. Subsequently, a habitat suitability prediction at a finer scale was used to estimate landscape resistance, starting from which, we modelled dispersal corridors among areas currently occupied by the species using a factorial least cost path and a cumulative resistant kernel approach. Our results indicated a moderate potential for large parts of the study region to support the occurrence of golden jackal family groups, whose presence seems to be mainly driven by the presence of wide areas covered by broadleaved forests and shrublands and by the absence of wide intensive agricultural areas. The predicted connectivity networks showed that three main permeable corridors are likely to connect golden jackal occurrence areas within the study region, while all the other corridors are characterized by a very low path density. Both the habitat selection and connectivity analyses showed a strong negative impact of the intensive cultivated plain on species stable presence and movement providing critical information for the conservation of the golden jackal in Italy.

Habitat selection and density of the Barbary partridge in Sardinia, Mediterranean Sea - Gianpasquale Chiatante; Anna Vidus Rosin; Claudia Elisa Cinerari; Marco Lombardini; Marco Murru; Alberto Meriggi (European Journal of Wildlife Research, 2020)

The occurrence and density of three sympatric corvids in a Mediterranean agroecosystem explained by land use - Chiatante Gianpasquale; Meriggi Alberto (Journal of Ornithology, 2019)

Seasonal spatial ecology of the wild boar in a peri-urban area - Sara Amendolia; Marco Lombardini; Paola Pierucci; Alberto Meriggi (Mammal Research, 2019)

Multi-scale habitat requirements of forest bird species in a highly fragmented landscape - Gianpasquale Chiatante; Zeno Porro; Arianna Musacchio; Arianna Bazzocchi; Alberto Meriggi (Journal of Ornithology, 2019)

Habitat requirements of Eurasian pine marten Martes martes in a Mediterranean environment - Marco Lombardini; Claudia E. Cinerari; Marco Murru; Anna Vidus Rosin; Linda Mazzoleni; Alberto Meriggi (Mammal Research, 2015)